CAPTIONS WRITING IN INSTAGRAM: UNDERSTANDING THE MEANING AND THE COMMUNICATIVE FUNCTION IN LEARNING A LANGUAGE - Diah Royani Meisani; Nidaan Nungky Chofiyya; Reli Handayani (Universitas Jambi, 2016)
This study was conducted to investigate the language functions used in captions written in Instagram and reveal the meaning behind it. It was undertaken by analyzing the captions written by Ani Yudhoyono in her personal Instagram. The descriptive qualitative design was implemented in the recent study. The result of the analysis revealed that all six elements of communication were found, namely addresser, context, message form, contact, common code, and addressee. Five functions of language and its combinations were being used in the captions in order to ensure message delivery. The language function mostly used was referential function with twenty five sentences used or 58.1%. The caption needs to use this function because Instagram photos require a lot of information to be informed to the followers in order to get the message of the photo through the caption. The meanings given were also varied, yet they were all positive.